Carbon Sequestration Projects in Desert Rural Areas and Lands of Iran: Participatory Management of Natural Resources Stabilized among Local Communities - Farhood Golmohammadi (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2026)
Today, the environment and natural resources are exposed to increasingly numerous interests and demands, which sometimes generate conflicts and the livelihood of millions of rural households worldwide is closely related to them. The current level of livelihood dependency of local livelihood on environmental income is reported as high in many developing countries. The Sustainable Development Goals (SDGs) highlight the links between human well-being, economic advancement, and a stable environment. As mentioned and discussed in this article, Carbon Sequestration Projects (CSPs) for Community-based Rural Development and Sustainable Natural Resources Management in Arid and Semi-arid lands of South Khorasan province, east of Iran, could have a tangible and important role for improving the environment and social conditions, problems and troubles in this border, frontier, isolated and deprived area of Iran. Advocacy, extension, and development of the community-based and button-up approach in the field of natural resources management at the national level must be considered. Objectives of this outcome are to: Introduce the participatory approach and the methods used by CSP to national and provincial decision makers, train and advocate the participatory model of natural resources management, form a nationwide working group, incorporate practices and the community-based approach of CSP into the Iranian National Socio-Economic Development Plan. Introducing more diverse sets of profitable and less environmentally reliant income-generating activities, along with the development of a more educated rural population, will stimulate development in rural areas, alleviating environmental pressure on environmentally fragile ecosystems. CSP mainly addressed ensuring the sustainability of village development groups. One of the main objectives of CSP is to have the concept of participatory management of natural resources stabilized among local communities. In this article, the author discusses and states the most important aspects of CSPs for Community-based Rural Development and Sustainable Natural Resources Management in Arid and Semi-arid lands in South Khorasan province, east of Iran.